Using gamification to create brand love in online retailing: Brand engagement and value co-creation perspective - Malik, Garima; Sharma, Piyush; Leung, Tak Yan (2023)
Gamification has emerged as a popular approach to use a virtual platform in combination with social media and other emerging digital platforms to enhance brand engagement. We investigate the focal roles of co-creation and brand love in the impact of brand engagement on brand loyalty and advocacy in a gamified online retailing platform. We use a multi-method approach with two consumer surveys (Gen Y=389 and Gen Z= 496) and a sentiment analysis of user-generated content with tweets about gamification in the context of online retailing. Results confirm a positive link for social and emotional (but not cognitive) brand engagement with value co-creation. Brand love is positively associated with both brand advocacy and loyalty. Finally, brand trust fully moderates the relationship between value co-creation and brand love. Besides adding to the current research on brand love, gamification, and consumer brand engagement, these findings also provide useful insights to online retailers for using gamification to drive their customer engagement and value co-creation efforts to create brand love that in turn would lead to customer loyalty and advocacy.